Al-Gahazali’s thoughts on the effects of music and singing upon the heart and the body and their impact on present-day Malaysian society - Jahnichen, Gisa (Center for Promoting Ideas, 2012)
Al-Gahzali (1058-1111) wrote his essay on ‘Music and Singing’ to clarify his thoughts on the Effects of Music and Singing upon the Heart and the Body. He criticizes listening to music and singing because they are associated with gatherings where wine is drunk and lustful entertainment is deliberately provoked. The only kind of music and singing to be allowed is that of religious and heroic songs and modest pieces. In his opinion, an excess of music and singing should be avoided. The same is said of dancing, which may be practised or watched as long as it does not arouse desire and aims at encouraging sinful acts. Over the centuries, Al-Ghazali’s thoughts circulated among the ‘learned’ in the Muslim communities of present-day Malaysia. As one result, specific ideas were shaped on the relatedness between music, singing, dance on the one hand and heart and body on the other. This paper focuses on the impact of these ideas on the understanding of a culturally defined permissibility of musical embodiment. Moreover, actual changes through global knowledge access and through social contradictions within the multi-cultural Malaysian society are discussed employing an epistemological approach to key terms such as ecstasy, sin, control, fear, sorrow and joy.